Treinamento resistido e reposição hormonal aumentam a atividade das metaloproteinases-2 e a qualidade de osso de ratas ovariectomizadas - Souza, Markus Vinicius Campos (Universidade Federal de São Carlos, 2016)
Purpose: The aim of the present study was to investigate the influence of resistance training (RT) and hormone replacement (HR) on MMP-2 activity, biomechanical and physical properties bone of ovariectomized (OVX) rats. Methods: Sprague-Dawley female rats were grouped into six experimental groups (n = 11 per group): shamoperated sedentary (SHAM Sed), ovariectomized sedentary (OVX Sed), sham-operated resistance training (SHAM RT), ovariectomized resistance training (OVX RT),(OVX Sed-HR), and OVX RT-HR. HR groups received implanted silastic capsules with a 5% solution of 17β-estradiol (50 mg 17β-estradiol/ml of sunflower oil). In a 12-week RT period (27 sessions; 4–9 climbs) the animals climbed a 1.1 m vertical ladder with weights attached to their tails. Biomechanical and physical bone analyses were performed using a universal testing machine, and MMP-2 activity analysis was done by zymography. Results: Bone density and bone mineral content was higher in the RT and HR groups. The MMP-2 activity was higher in the RT and HR groups. The biomechanical analysis (stiffness, fracture load and maximum load) demonstrated better bone tissue quality in the RT associated with HR. Conclusion: The RT alone as well as when it is associated with HR was efficient in increasing MMP-2 activity, biomechanical and biophysical properties bone of ovariectomized rats.
Keywords: Osteoporose; Treinamento resistido; Ovariectomia; Reposição hormonal; Matrix metaloprotease 2 (MMP-2); Osteoporosis; Resistance training; Ovariectomy; Hormone replacement; Metalloproteinase-2 (MMP-2); CIENCIAS BIOLOGICAS